2011
DOI: 10.1136/sti.2010.044560
|View full text |Cite
|
Sign up to set email alerts
|

Increased HIV testing and reduced undiagnosed infection among gay men in Scotland, 2005-8: support for the opt-out testing policy?

Abstract: ObjectiveTo examine changes in HIV testing and undiagnosed infection among men who have sex with men in Scotland between 2005 and 2008.MethodsSelf-completed questionnaires and Orasure oral fluid collection kits were distributed to men visiting the commercial gay scene in Glasgow and Edinburgh.ResultsQuestionnaires and oral fluid specimens were provided by 1350 men (51.6% response rate) in 2005 and 1277 (59.7% response rate) in 2008. 2572 men were eligible for inclusion in the analyses. Recent HIV testing incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…Repeat testing among MSM has been associated with a history of STIs, higher number of sexual partners, having oral or unprotected insertive anal sex, and knowing someone with HIV infection 42 44. In this review, non-reattenders in response to recall were more likely to be HIV-positive,31 in keeping with studies that have compared sexual risk among those that test for HIV compared with those that do not 31 45 46…”
Section: Discussionsupporting
confidence: 62%
“…Repeat testing among MSM has been associated with a history of STIs, higher number of sexual partners, having oral or unprotected insertive anal sex, and knowing someone with HIV infection 42 44. In this review, non-reattenders in response to recall were more likely to be HIV-positive,31 in keeping with studies that have compared sexual risk among those that test for HIV compared with those that do not 31 45 46…”
Section: Discussionsupporting
confidence: 62%
“…However, despite guidance for more frequent HIV testing,25 the little evidence there is on the acceptability, feasibility and effectiveness of increased recall frequency is conflicting 11 26 27. Therefore, further studies are required to determine optimal frequency of HIV testing 27…”
Section: Discussionmentioning
confidence: 99%
“…National audits examined the proportion of MSM offered and taking up an HIV test,9 10 and surveys have investigated the association between recent HIV testing and HIV infection 11. To our knowledge, there has been no national analysis of frequency of HIV testing or characterisation of behavioural interventions offered in SH clinics.…”
Section: Introductionmentioning
confidence: 99%
“…This may, in part, be explained by a lack of consistency between the HIV testing guidelines and national guidelines for the specialties involved [95]; for example, UK guidelines for the management of peripheral neuropathy do not mention HIV testing even though HIV guidelines name this as a clinical indicator for testing [211]. However, there have been some successes -a Scottish study of MSM testing rates showed significant increases from 2005 to 2008 in those ever tested (60.8 to 74.6%) and those tested in the last 12 months (34 to 48.3%) [97], and UK surveillance data shows a small increase in diagnoses made in primary and acute medical services. The possibility of consenting all surgical patients to point-of-care HIV testing in the case of needlestick injury to staff has also been raised in a recent paper [98].…”
Section: Reducing Late Diagnosismentioning
confidence: 99%